EVALUATING THE EFFECTIVENESS OF ESG INVESTING: A REVIEW OF FINANCIAL PERFORMANCE, REAL-WORLD IMPACT, AND MEASUREMENT CHALLENGES - Otabek Pardabaev (TADQIQOTLAR, 2026)
Abstract Environmental, Social, and Governance (ESG) investing has become a central feature of modern financial markets, yet its effectiveness remains the subject of intense academic debate. This review synthesizes key findings from influential studies across three core dimensions of ESG effectiveness: financial performance, real-world impact, and measurement quality. The evidence on financial performance reveals a divide between empirical studies reporting neutral-to-positive risk-adjusted returns and theoretical models suggesting that strong investor demand may lower future expected returns. Real-world impact literature shows that active ownership can influence corporate behavior, whereas ESG fund flows exert limited effects on firms’ cost of capital or environmental outcomes. Finally, research on ESG measurement highlights significant rating divergence and methodological inconsistencies, raising concerns about the reliability of ESG metrics used for capital allocation. By focusing on the most impactful contributions, this review clarifies the major points of convergence and contradiction within the ESG literature and provides a concise foundation for future research and policy discussion.